PEMIKIRAN ORIENTALIS JONATHAN BROWN TERKAIT PENELITIAN HADIS - Nur Hamidah Pulungan; Nur Fadhilah Syam (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2023)
Jonathan Brown is known as an orientalist who has converted to Islam and is still alive at the time this article was published. His thoughts on the study of Hadith did not escape in-depth research and studies. This research focuses on the canonization of the book Bukhari which is one of Jonathan's thoughts regarding the Hadith. This research which is a literature review concludes that in Jonathan's research, he borrowed the canonization methodology which is well known in the study of Christian theology. For Jhon, the book Sahih Bukhari can be the main source in prioritizing Hadith studies because it has gone through the stages of study and criticism from Hadith expert scholars who then created other books of hadith genres such as the books of 'ilal and mustakhraj. The role of al-Hakim became very important in spreading the book Sahih Bukhari. Jonathan Brown dikenal sebagai orientalis yang ternyata telah memeluk Islam dan masih hidup hingga tulisan ini diterbitkan. Pemikirannya terhadap kajian Hadis tidak luput dari penelitian dan kajian yang mendalam. Penelitian ini berfokus pada kanonisasi kitab Bukhari yang merupakan salah satu pemikiran Jonathan terkait Hadis. Penelitian yang bersifat kajian pustaka ini menyimpulkan hasil bahwa dalam penelitian Jonathan tersebut, ia meminjam metodologi kanonisasi yang terkenal dalam kajian teologi Kristiani. Bagi Jhon, kitab Shahih Bukhari dapat menjadi sumber utama dalam prioritas kajian Hadis karena telah melewati tahap pengkajian dan kritik dari ulama ahli Hadis yang lantas menciptakan kitab genre hadis lainnya seperti kitab ‘ilal dan mustakhraj. Peran al-Hakim menjadi sangat penting dalam penyebaran kitab Shahih Bukhari.